2002
DOI: 10.1046/j.1532-5415.2002.50465.x
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy Reveals Similar White Matter Biochemical Changes in Patients with Chronic Hypertension and Early Alzheimer's Disease

Abstract: In this study, cognitively intact chronic hypertensive older patients had a higher white matter myoinositol/creatine ratio compared with healthy older subjects, suggesting that myoinositol may be a sensitive marker of the effects of chronic hypertension on the brain. Moreover, the similar increase of myoinositol/creatine ratio in patients with hypertension and in those with early AD provides further evidence of common brain changes with these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
2
20
1
1
Order By: Relevance
“…The increase in PPL mI/Cr in our series agrees with a previous report showing higher mI/Cr values in the peritrigonal white matter of patients with asymptomatic hypertension. 5 Regarding the changes in frontal NAA/Cr ratio, the ratio drop in our resistant hypertensive patients is in agreement with two recent chemical-shift imaging reports involving the white matter of the centrum semiovale 21 and particular areas in the white and gray matters. 22 These studies showed decreasing NAA concentrations associated with increasing severity of disease 21 and NAA/Cr decreases in the gray matter of hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The increase in PPL mI/Cr in our series agrees with a previous report showing higher mI/Cr values in the peritrigonal white matter of patients with asymptomatic hypertension. 5 Regarding the changes in frontal NAA/Cr ratio, the ratio drop in our resistant hypertensive patients is in agreement with two recent chemical-shift imaging reports involving the white matter of the centrum semiovale 21 and particular areas in the white and gray matters. 22 These studies showed decreasing NAA concentrations associated with increasing severity of disease 21 and NAA/Cr decreases in the gray matter of hypertensive patients.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the originality of these results also dwells in the sample characteristics. Although, in the other quoted papers, comparisons were carried out between groups of normal vs asymptomatic hypertensive patients, 5,22 symptomatic vs asymptomatic hypertensive patients, 21 or treated vs untreated patients, 23 we focused on the effect of medical treatment by comparing two groups of treated asymptomatic hypertensive patients with opposing outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is involved in several important cellular processes in the brain as a marker of phospholipid turnover and gliosis, a secondary messenger and a detoxifying molecule (Catani et al, 2002;LopezVillegas et al, 1997;Shonk et al, 1995). In addition to depression, mI has been observed as elevated in patients with Alzheimer's disease, mild cognitive impairment (Huang et al, 1999;Kantarci et al, 2000;, primary progressive aphasia (Catani et al, 2003), and hypertension (Catani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%